Head shape analysis of National Football League Players - Park, G.; Gabler, L. F.; Bailey, A. M.; Dau, N. Z.; Sherwood, C.; Crandall, J. R.; Arbogast, K. B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Understanding the size and shape variations of the head is important to the design of football helmets used to mitigate the risk of head injury. Current guidelines for selecting helmets use only the circumference of the player`s head to determine an appropriate size that may not offer the best fit and protection for every player. The goal of this study was to quantify key measurements of head shape to sufficiently characterize variability among players in the National Football League (NFL), focusing on the shape variation of the cranial region. Statistical shape analysis was performed on three-dimensional head scans of 87 contemporary NFL players to identify key features of head shape variability among the players` heads. The principal component analysis revealed two factors that explained 87% of the head shape variance: (1) height and length of the head in the sagittal plane and (2) prominent back of the head with an oval shape in the transverse plane versus prominent forehead with a round shape. Four head shape measurements (circumference, length, breadth, and height) were then defined and quantified to describe the first two principal components. This information can facilitate improvements in the design of football helmets.